Banco Sabadell Acquires Banco CAM: Leveraging a Cloud Computing Strategy. Issue 1 (May 2015) - Busquets, Javier; Álvarez, Conchita
In a deep financial crisis in Spain, Banco Sabadell won a competitive bid to acquire Banco CAM for the price of €1. The President of Banco Sabadell Josep Oliu announced at a press conference on the 8 December 2012 that BCAM, a similar size to its acquirer, must be integrated in less than 1 year. Banco Sabadell management expected €331 million in synergies from 2012 to 2014. The case focuses on Miquel Montes, the new CEO in Banco CAM, and his team; Federico Rodriguez, new Chief Operations Officer; and Carles Abarca, new Chief Information Officer. Banco Sabadell had developed a cloud computing architecture never tested before in mergers and acquisitions (M&A). Despite Sabadell management's strong and proven experience of M&As, there were risks associated with the benefits. Students need to understand both in order to understand how to plan in such situations.